How the People Acquire Language?: A Case Study on Virendra Language Acquisition - Tatu Zakiyatun Nufus; Atik Yuliani (English Language in Focus (ELIF), 2020)
The language acquisition process can be seen as a running parallel throughout a child’s life every day, it happened for every human who interacts with other people to share information since they were a child. It looks closely at the acquisition of the early age of Virendra, he was a child under 5 age who lives in the Sundanese environment and he is not familiar with English as a foreign language. Virendra was familiar with Arabic literature previously in his house, and he knows English in the formal school of his Playgroup up to now in kindergarten, the writer tried to report this case using a descriptive method. The data is collected while he was used the language in the school and how his parents influence his language acquisition in the house. And it is conducted to know how well Virendra’s comprehension in producing language. Beside it, this study is expected to the parents to lead the child in using language.